Genetic and physical characterization of lysogeny by bacteriophage MX8 in Myxococcus xanthus. - Orndorff, P (1983)
Myxophage MX8 can initiate a lysogenic cycle in Myxococcus xanthus. The lysogenic phage was gentically stable in vegetative cells and persisted in the latent state through many cell generations in the absence of extracellular phage reinfection. The latent state also was stable during the host developmental cycle, since myxospores transmitted latent MX8 genetic information to future progeny cells. DNA hybridization experiments to probe the structure of the lysogenic phage provided physical evidence that MX8 formed a prophage. During lysogenization, MX8 DNA was cut at a specific site (attP) on phage DNA, and we have concluded that genetic recombination between attP and a bacterial DNA site (attB) leads to integration of MX8 DNA and formation of stable MX8 prophage. The genetic and physical properties of MX8 that we describe should make MX8 useful in the analysis of development of M. xanthus by genetic methods.